The Congenital Malformations in White Pregnant Mice Fetus Induced by Metformin Drug During 6-18 Days of Gestation - Toama, Faeza Nasir; Hamid, Aziz Khalid; Hamid, Aziz Khalid; Jameel, Asmat Jamal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The metformin drug  is anti-hyperglycemia  and known to cross the placenta  which leads to the fetus during pregnancy .The aim of this study is to  define the drug  effects in the fetus growth . The doses  used , therapeutic dose ( 0.18 & 0.53 ) mg\25g body weight  and over dose ( 1.8 & 2.85) mg\ 25g body weight , administrated orally  at the beginning organogenesis stage at ( 6 -18 ) day of pregnancy in the morning . A total ( 50 ) animal  were divided into five groups .The first group control not treated , 2nd group  treated with (0.18) mg , 3rd group  with  ( 0.53 ) mg , 4th group with ( 1.8 ) mg and 5th group with    ( 2.85 ) mg .  In this study noted  some congenital malformations in the fetus compared with  normal control group , which included in the 2nd  and 3rd  group ( irregular body level , exophthalmia , micromelia , elevated some  hand fingers , simple club foot , torsion tail and wrinkle skin ) while the defects was larger in the 4th  and 5th group ( trunk abnormalities like C Shape , big head ( scaphocethaly) , cranial flexure , prosencephaly, short neck , micromelia , syndactyly  some of hand fingers and others  hemimelia  , torsion tail and some aquiline , sharply club foot  and spina bifida ) . It is  mentioning  that the malformations was less in the 2nd group  treated with (0.18) mg of  the drug  . The treatment with metformin drug during pregnancy induced the congenital malformations .